The Effect Of Alloying Elements On Wear Behaviour Of Ni-Al - Ishak, Mohamad Izha (2004)

(untitled)
Considerable amount of research has been performed on nickel aluminide (NiAl) over the last decade, with an exponential increase in effort occurring over the last few years. The enormouS potential of NiAI systems mainly from its many attractive properties, such as high oxidation and corrosion resistance and relatively low densities, combined with the ability to retain strength and stiffness at elevated temperature. Furthermore, NiAI has emerged as potential high temperature structural material because of its high melting temperature. The main objective of this research is to synthesis Ni-Al by reaction sintering of partial mechanically alloyed powder and to evaluate the wear behaviour of the prepared materials. Banyak penyelidikan telah dijalankan ke atas NiAI sejak sedekad yang lalu dan usaha terhadap kajiannya meningkat sejak beberapa tahun yang lepas. NiAI mempunyai potensi besar yang disumbangkan oleh sifat-sifatnya yang menarik seperti rintangan pengoksidaan dan kakisan yang tinggi dan ketumpatan yang rendah. Sifat-sifat ini apabila digabungkan mempunyai keupayaan untuk menahan kekuatan dan kekakuan pada suhu yang tinggi. Selain daripada itu, NiAI berpotensi untuk digunakan sebagai bahan struktur pada suhu tinggi disebabkan oleh takat lebumya yang tinggi dan konduktiviti terma yang baik. Tujuan utama penyelidikan adalah untuk sintesis 1ı-AI melalui persinteran reaktif dan mengkaji kelakuan haus sampel yang disediakan.